2021
DOI: 10.1021/acs.nanolett.1c00182
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Electrical Excitation of Distinct Modes in Plasmonic Waveguides

Abstract: The electrical excitation of guided plasmonic modes at the nanoscale enables integration of optical nanocircuitry into nanoelectronics. In this context, exciting plasmons with a distinct modal field profile constitutes a key advantage over conventional single-mode integrated photonics. Here, we demonstrate the selective electrical excitation of the lowest-order symmetric and antisymmetric plasmonic modes in a two-wire transmission line. We achieve mode selectivity by precisely positioning nanoscale excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The emission spectrum is essentially broadband, which is fundamentally related to the nature of the IET process, producing photonic and/or plasmonic excitations of all energies below eV bias . ,,, From the measured emission power at the nanowire tip regions together with the tunneling current of ∼7 μA at 2.2 V, the EQE for the waveguided plasmonic output channel in both directions was estimated to be 2 × 10 –6 (Supporting Information Section 6). This value is about 10 times lower than that of tunneling devices with waveguided output based on nanoantenna designs , or scanning tunneling microscope tips (tunneling current ∼10 nA), which is mainly due to the lower LDOS of the MIG-TJs. At the same time, the MIG-TJs demonstrated here can provide a much higher overall waveguided optical power important for practical applications because of their higher electrical input power provided by the longer junction length.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The emission spectrum is essentially broadband, which is fundamentally related to the nature of the IET process, producing photonic and/or plasmonic excitations of all energies below eV bias . ,,, From the measured emission power at the nanowire tip regions together with the tunneling current of ∼7 μA at 2.2 V, the EQE for the waveguided plasmonic output channel in both directions was estimated to be 2 × 10 –6 (Supporting Information Section 6). This value is about 10 times lower than that of tunneling devices with waveguided output based on nanoantenna designs , or scanning tunneling microscope tips (tunneling current ∼10 nA), which is mainly due to the lower LDOS of the MIG-TJs. At the same time, the MIG-TJs demonstrated here can provide a much higher overall waveguided optical power important for practical applications because of their higher electrical input power provided by the longer junction length.…”
mentioning
confidence: 76%
“…It is determined not only by the IET efficiency (the ratio between the inelastic tunneling rate related to the excitation of electromagnetic modes in the junction and the total electron tunneling rate) but also by the loss of these modes in the junction region and their outcoupling efficiency to the desired output, such as free-space light and waveguided plasmonic or photonic modes. , Recently, by combining tunnel junctions with optical nanoantennas, it was shown that the efficiency of generation of free-space photons can be greatly enhanced via the large local density of optical states (LDOS) in the tunnel junctions (which greatly increases the IET efficiency) and the high far-field radiation efficiency of the optical nanoantennas, ,, ,,, with the EQE of light emission reaching the levels up to ∼2% . However, it remains a great challenge to couple the metal–insulator–metal (MIM) plasmonic modes excited in the nanoscale tunneling gap between the two electrodes to technologically appealing modes of a waveguide ,, as opposed to omnidirectional emission into free-space light. The two main factors that limit the EQE are the high propagation loss of the highly confined MIM plasmonic modes and the dramatic momentum and modal size mismatch between the highly confined MIM plasmonic modes and the plasmonic or photonic waveguided modes, ,,, which greatly limit the outcoupling of the excited MIM plasmonic signal to the optical circuits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–insulator–metal (MIM) tunneling junctions have been intensely studied as potential nanosources of surface plasmons and light, though other material systems and geometries have also been considered. The tunneling junction used in this work is shown schematically in Figure a; two metal electrodes (here a gold nanocube and a thin (50 nm) gold film) are separated by an insulating molecular layer (1,8-octanedithiols, ∼1 nm thick).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrate THG in plasmonic waveguides in a two‐wire transmission line (TWTL) configuration, [ 36 ] where two Ag slabs are placed in nanoscale proximity with a NOP cladding as the active medium, as illustrated in Figure 1 . This type of platform supports symmetric (S) and antisymmetric (AS) plasmonic modes [ 37 ] and is in favor of modal phase matching (MPM), [ 14 , 38 ] with operation wavelengths extending from the optical to the near‐infrared spectral range.…”
Section: Introductionmentioning
confidence: 99%